Sistem Manajemen Kinerja Berbasis pada Input Proses dan Output MTs Miftahul Falah Diski - Mulkan Hasibuan; Edy Rosadi (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
This research was conducted to get an overview of the performance system at MTs Miftahul Falah Diski where the madrasa foundation is actively carrying out its activities despite the covid 19 pandemic in order to improve teacher performance during the covid 19 pandemic. The research approach that is more appropriate to use is a qualitative approach that is the reason why researchers choose the approach method qualitative has a natural background as a data source. The results of the research on performance system planning for teachers during the covid 19 pandemic Miftahul Falah Diski. Organizing the performance system by dividing tasks to the deputy head of Madrasah Tsanawiyah to improve performance in terms of input and output at the madrasa. Implementation of the online meeting performance system plan, individual coaching and guidance. The madrasa performance system evaluation activity to determine the teacher's teaching performance becomes measurable for the implementation of further actions to promote learning.